Determination of the Thermal Insulation for the Model Building Approach and the Global Effects in Turkey. (14th August 2014) - Onan, Cenk
Abstract : One of the most important considerations to be considered in the design of energy efficient buildings is the thickness of the insulation to be applied to the building. In this study the existing building stock in Turkey has been investigated depending on parameters such as the height and the area. A model building has been created covering all of these buildings. Fuel emission reduction of combustion system was calculated in the case of insulation applied to this model building. Heat loss of the existing building stock and exhaust emissions and the contribution to the country's economy with the model building methodology are also determined. The results show that the optimum insulation thicknesses vary between 3.21 and 7.12 cm, the energy savings vary between 9.23 US$/m 2 and 43.95 US$/m 2, and the payback periods vary between 1 and 8.8 years depending on the regions. As a result of the study when the optimum insulation thickness is applied in the model building, the total energy savings for the country are calculated to be 41.7 billion US$. And also total CO2 emissions for the country are calculated to be 57.2 billion kg CO2 per year after insulation.